Cashless society: Tantangan dan Kesiapan Masyarakat di Kabupaten Fakfak - Muh. Fachruddin; Basri, Hasan; Nur, Muhammad (Jurnal Informasi, Sains dan Teknologi, 2025)
The development of information and communication technology has significantly transformed the way people conduct financial transactions. One prominent shift is the transition from cash-based transactions to non-cash payment systems, commonly referred to as a cashless society. The core concept of a cashless society relies on transactions conducted through electronic payment instruments. This study aims to examine the challenges and readiness of the Fakfak Regency community in navigating the transition toward a cashless society. Using a qualitative approach, data were collected through surveys and in-depth interviews with various stakeholders, including the general public, local government, financial institutions, and local business actors. Most existing studies on cashless society predominantly focus on urban areas and regions with well-developed digital infrastructure. This research offers novelty by exploring the challenges and readiness of communities in Fakfak Regency, one of the 3T (frontier, outermost, and disadvantaged) regions in West Papua, characterized by limited digital infrastructure, low financial literacy, and a significant digital divide. Data analysis was carried out using the Technology Acceptance Model (TAM) to identify factors influencing the adoption of non-cash payment technologies. The findings indicate that the community in Fakfak Regency is not yet fully prepared for a cashless society. The region remains in the early stages of adopting non-cash transactions and faces various obstacles, including limited technological capability and insufficient infrastructure to support improvements in financial and digital literacy. This study provides important contributions by presenting an empirical picture of cashless adoption in a 3T region and offers valuable insights for developing more inclusive, adaptive, and contextually appropriate policies for the local transition toward a cashless society.